Mabuia wirzi Roux, 1925 (Squamata: Scincidae), an overlooked synonym of Dasia olivacea Gray, 1839, with notes on the synonymy of Dasia olivacea - Shea, Glenn M.; Iskandar, Djoko T. (Zootaxa, 2020)
Almost a century ago, the Swiss herpetologist Jean Roux described a new skink species, Mabuia wirzi, from a single specimen from Pulau Nias, an island on the west coast of Sumatra in Indonesia (Roux 1925). The specimen was part of a small collection of reptiles and amphibians made on Nias by the ethnologist Paul Wirz (29.v.1892–1955.i.30), who worked on Nias in 1925 and 1926 (Wirz 1928, 1929). Roux’s paper was published in October 1925, and hence the specimen would have come from Wirz’s first expedition, and would have been only recently preserved at the time of description.